A large refined catalog of earthquake relocations and focal mechanisms for the Island of Hawai'i and its seismotectonic implications. Issue 7 (9th July 2016) - Lin, Guoqing; Okubo, Paul G.
Abstract: We present high‐quality focal mechanisms based on a refined earthquake location catalog for the Island of Hawai'i, focusing on Mauna Loa and Kīlauea volcanoes. The relocation catalog is based on first‐arrival times and waveform data of both compressional and shear waves for about 180, 000 events on and near the Island of Hawai'i between 1986 and 2009 recorded by the seismic stations at the Hawaiian Volcano Observatory. We relocate all the earthquakes by applying ray tracing through an existing three‐dimensional velocity model, similar event cluster analysis, and a differential‐time relocation method. The resulting location catalog represents an expansion of previous relocation studies, covering a longer time period and consisting of more events with well‐constrained absolute locations. The focal mechanisms are obtained based on the compressional‐wave first‐motion polarities and compressional‐to‐shear wave amplitude ratios by applying the HASH program to the waveform cross correlation relocated earthquakes. Overall, the good‐quality (defined by the HASH parameters) focal solutions are dominated by normal faulting in our study area, especially in the active Ka'ōiki and Hīlea seismic zones. Kīlauea caldera is characterized by a mixture of approximately equal numbers of normal, strike‐slip, and reverse faults, whereas its south flank has slightly fewer strike‐slip events. Our relocation and focal mechanism results will be useful for mapping the seismic stress and strain fields and for understanding the seismic‐volcanic‐tectonic relationships within the magmatic systems. Key Points: The active seismic zones are dominated by normal faulting in Hawaii Kilauea caldera is characterized by a mixture of approximately equal numbers of normal, strike‐slip, and reverse faults A new earthquake relocation and focal mechanism catalog is made available